(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe dietary habits and levels of physical activity, and to analyze their associations with overweight and obesity status among students of the Faculty of Health Sciences and Nutrition at Vietnam College of Medical Technology and Pharmacy in 2025. Methods: A case-control study was conducted among 303 students using a matched convenience sampling method. Overweight and obesity status were assessed using BMI. The case group included 101 students with BMI ≥ 25 kg/m², while the control group consisted of 202 students with BMI ranging from 18.5-24.9 kg/m². Data on general characteristics, dietary habits, frequency of food consumption, and physical activity levels were collected using a structured questionnaire. Physical activity was assessed using the GPAQ questionnaire. Data were entered using EpiData 3.0 software and analyzed with SPSS version 20.0 software. Statistical analyses included descriptive statistics, Chi-square tests, and logistic regression, with p < 0.05 considered statistically significant. Results: Among 101 overweight and obese participants, 81 were female. Female students had a higher prevalence than males across all categories (77.8%). Unhealthy dietary behaviors were more prevalent among overweight and obese students, including late-night eating ≥ 2 times/week (39.6%), frequent meat consumption ≥ 4 times/week (54.4%), and skipping breakfast ≥ 3 times/week (32.7%). The frequency of fast food consumption (OR = 2.14), fried foods (OR = 1.68), and sugar-sweetened beverages (OR = 3.90) was significantly associated with overweight and obesity (p < 0.05). Low levels of physical activity were also significantly associated with overweight and obesity (p = 0.003). Multivariable logistic regression analysis indicated that insufficient physical activity (≥ 3-4 times/week not achieved) and low physical activity levels were independently associated with overweight and obesity. Conclusions: Certain unhealthy dietary habits and low levels of physical activity are associated with an increased risk of overweight and obesity among students.